Novel High-grade Endometrial Stromal Sarcoma: A Morphologic Mimicker of Myxoid Leiomyosarcoma. (January 2017) - Hoang, Lien N.; Aneja, Amandeep; Conlon, Niamh; Delair, Deborah F.; Middha, Sumit; Benayed, Ryma; Hensley, Martee L.; Park, Kay J.; Hollmann, Travis J.; Hameed, Meera R.; Antonescu, Cristina R.; Soslow, Robert A.; et al.
Abstract : Endometrial stromal sarcomas (ESS) are often underpinned by recurrent chromosomal translocations resulting in the fusion of genes involved in epigenetic regulation. To date, only YWHAE-NUTM2 rearrangements are associated with distinctive high-grade morphology and aggressive clinical behavior. We identified 3 ESS morphologically mimicking myxoid leiomyosarcoma of the uterus and sought to describe their unique histopathologic features and identify genetic alterations using next-generation sequencing. All cases displayed predominantly spindled cells associated with abundant myxoid stroma and brisk mitotic activity. Tumors involved the endometrium and demonstrated tongue-like myometrial infiltration. All 3 were associated with an aggressive clinical course, including multisite bony metastases in 1 patient, progressive peritoneal disease after chemotherapy in another, and metastases to the lung and skin in the last patient. All 3 ESS were found to harbor ZC3H7B-BCOR gene fusions by targeted sequencing and fluorescence in situ hybridization. On the basis of the review of these cases, we find that ESS with ZC3H7B-BCOR fusion constitutes a novel type of high-grade ESS and shares significant morphologic overlap with myxoid leiomyosarcoma.